Characteristics of xylazine‐related deaths in West Virginia—Xylazine‐related deaths. Issue 3 (12th December 2022) - Sibbesen, Julie; Abate, Marie A.; Dai, Zheng; Smith, Gordon S.; Lundstrom, Eric; Kraner, James C.; Mock, Allen R.
Abstract: Background and Objectives: The involvement of xylazine, a veterinary drug, in West Virginia (WV) human drug‐related deaths was examined. Methods: WV drug deaths from 2019 (when xylazine was first identified) to mid‐2021. Characteristics including toxicology findings were compared between xylazine and nonxylazine deaths. Results: Of 3292 drug deaths, 117 involved xylazine, and the proportions of deaths with it have increased (1% [2019] to 5% [mid‐2021)]. Xylazine decedents had more cointoxicants, with fentanyl (98%) predominant followed by methamphetamine. Xylazine decedents had a significantly greater history of drug or alcohol misuse and hepatic disease. Conclusions and Scientific Significance: In one of the largest analyses of xylazine‐involved deaths in a predominantly rural state, identification of xylazine was increasing with multiple cointoxicants (especially fentanyl), and was present in a few deaths with only one other substance involved. Health professionals should be aware of possible enhanced toxicity from xylazine ingestion especially since naloxone does not reverse xylazine's adverse effects.